Assessment of sarcopenia as an independent nutritional indicator in pediatric inflammatory bowel disease - Arcucci, Maria Soledad; Demeco, Cristian; Kreindel, Tamara; Orsi, Marina; Gallo, Julieta; Busoni, Veronica; D’Agostino, Daniel (Open Science Journal, 2024)
Objective: To evaluate the presence of sarcopenia in a cohort of patients with pediatric inflammatory bowel disease (pIBD) and compare it to the presence of malnutrition according to body mass index (BMI). Methods: Descriptive study of patients under 18 years of age with IBD who underwent magnetic resonance enterography (MRE) between June 2018 and June 2022, followed at a University Hospital in Argentina. Clinical characteristics and anthropometric data were collected, and BMI and standard deviations were calculated. Total Psoas Muscle Area (tPMA) at levels L3–4 and L4–5 was compared with pediatric age and sex-specific growth curves. Results: We included 40 patients (50% females), 16 (40%) with Crohn's disease, and 24 (60%) with ulcerative colitis, mean age 9 years (IQR 3-13). The median time to MRE was 3 months after diagnosis (IQR 33 days- 1.5 years). In our cohort, 40% of patients had tPMA below the 5th percentile (z score -2). In contrast, only 3 patients (7.5%) had a BMI z score < -2. During follow-up, there was no significant difference in the use of biologics or number of relapses between patients with and without sarcopenia. Conclusions: Our cohort of pIBD had lower muscle mass than reference values, even in the short term. Our data show that sarcopenia can also be present despite a normal BMI. This finding reinforces the idea that sarcopenia could be an anthropometry-independent indicator of nutritional status and frailty in pIBD.